Comparing the Frequencies of 450 Mhz and 750 Mhz using GPR in Investigating Archaeological Features in (Borsippa) Site, Babylon, Iraq - Kareem, Hamza A.; Abd, Najah A. (Iraqi Journal of Science, 2024)
Mala GX (Ground Explorer) conducted the survey using two different antennas: 450 MHz and 750 MHz. Data for the 450 MHz antenna were collected in a grid, while data for the 750 MHz antenna were collected in parallel profiles at the same location above the 450 MHz profiles. After processing the data using GPR slice software, possible reflections of archaeological walls buried at different depths and with different extensions of 13 m, 7 m, 6 m, 5m, 3 and 2 m were identified. The reflections were clear and high in the 450 MHz antenna with a depth penetration of 3 meters and unclear and weak in the 750 MHz antenna with a depth penetration of 1 meter. When comparing the two antennas, it is possible to notice a match in the reflections of the walls, and some reflections are not identical in the 750 MHz antenna due to the high noise.